Investigating the efficacy of purified tannin extracts from underutilized temperate forages in reducing enteric methane emissions in vitro - Verma, S.; Akpensuen, T. T.; Wolffram, S.; Salminen, J.-P.; Taube, F.; Blank, R.; Kluß, C.; Malisch, C. S. (Nature Research, 2025)
The study investigated how the concentration and composition of purified tannin extracts, at various inclusion rates, affect the ruminal in vitro fermentation parameters. Tannin extracts were isolated from four different forage species: birdsfoot trefoil (Lotus corniculatus), sulla (Hedysarum coronarium), big trefoil (Lotus pedunculatus), and salad burnet (Sanguisorba minor). Plants extracts were purified by Sephadex LH-20 gel chromatography and analyzed by UPLC–ESI–MS/MS. The results showed a large variation among the extracts from different species in terms of tannin composition and structural features. The extracts from salad burnet were dominated by hydrolysable tannins, comprising mainly ellagitannins. The extracts derived from sulla and big trefoil contained predominantly proanthocyanidins (PA), primarily composed of prodelphinidins with high mean degree of polymerisation (mDP). Birdsfoot trefoil extracts comprised procyanidin-rich PAs with low mDP. To determine whether the combined presence of tannins and flavonoid together lead to synergistic or antagonistic effects, the tannin extracts were incubated both with or without rutin at concentrations of 10, 20, and 30 g/kg DM, using a base substrate of perennial ryegrass (Lolium perenne, control). In general, all the tannin extracts decreased methane (CH4) production compared to the control, while no significant effect of rutin was observed on both gas (GP) and CH4 production, neither pure, nor in the simultaneous presence of tannins. The highest CH4 reduction (15%, at 30 g/kg DM) was observed from sulla and big trefoil extracts compared to control, but this was also supplemented with a concomitant reduction in GP (11%) indicating a reduction in feed digestibility. The extracts from birdsfoot trefoil and salad burnet reduced CH4 by up to 12% without significantly reducing GP, indicating the importance of tannin composition on ruminal fermentation. © The Author(s) 2024.